Mechanical design and analysis of direct-plated-copper aluminum nitride substrates for enhancing thermal reliability. Issue 12 (December 2015) - Tsai, M.Y.; Huang, P.S.; Lin, C.H.; Wu, C.T.; Hu, S.C.
Abstract: Direct-plated-copper (DPC) aluminum nitride (AlN) substrate with a high thermal conductivity can provide a good alternative to conventional aluminum oxide (Al2 O3 ) substrate for better heat dissipation in the high-power module applications. However, the DPC AlN substrate suffers AlN crack initiating at the edge corner of Cu film during thermal cycling, due to the higher thermal expansion coefficient mismatch with copper material. This study is to resolve the AlN crack problem of DPC AlN substrate during thermal cycling and further to provide important parameters for mechanical design for ensuring good thermal reliability. Prior to the analysis, the out-of-plane deformation measurement of a Cu-AlN bi-material plate subject to the solder reflow heating and cooling is conducted for evaluating the material property of the plated Cu film and residual stresses induced from the manufacturing and solder reflow process. The results show the hysteresis and Bauschinger-like behaviors for the Cu-AlN plate during the solder-reflow heating and cooling. It is also found from the validated finite element simulation that the Cu-film wedge angle, length, and thickness significantly affect the maximum 1st principal stress of AlN during thermal cyclic loading, and the predicted failure mode and location based on the maximum 1st principal stress is consistent with experimental observation. The other factors, such as single-side and double-side Cu-film (sandwich-structure-alike) substrates, length difference of Cu films, and the nonlinear property of Cu film will be presented and discussed in detail as well. Highlights: To resolve crack problem of DPC AlN substrate during thermal cycling and provide parameters for good thermal reliability. To show the hysteresis and Bauschinger-like behaviors for a Cu-AlN bi-material plate under the solder reflow. To find out Cu-film wedge angle, length, and thickness significantly affect the maximum stress of AlN during thermal cycling. The predicted failure mode and location based on the maximum 1st principal stress of AlN is consistent with experiment. The nonlinear property of Cu-film can dramatically lower the maximum 1st principal stresses of AlN.